Meningkatkan Akses dan Kemampuan Literasi Digital di Era Informasi - Gustiana, Zelvi; Satria, Welnof (Jurnal Pengabdian Masyarakat, 2024)
In today's digital era, digital literacy is a fundamental skill that every individual must possess. The community service program to enhance Access and Capabilities in Digital Literacy in the Information Era aims to reduce the digital divide by improving digital literacy access and skills among the community, especially in underdeveloped areas. Through a series of training and workshops that include basic introductions to information technology, digital security, and assessing the credibility of online information, the program has successfully enhanced the digital literacy skills of its participants. Program evaluations indicate significant improvements in technology use and understanding of information security. Despite challenges such as infrastructure limitations and varied initial abilities among participants, flexible curriculum adaptations and teaching methods have helped overcome these barriers. This program not only provides direct benefits to participants but also has the potential to expand economic and educational opportunities and prepare the community for more active participation in social and cultural life in the digital age.